2020
DOI: 10.1038/s41598-020-68379-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired iloprost-induced platelet inhibition and phosphoproteome changes in patients with confirmed pseudohypoparathyroidism type Ia, linked to genetic mutations in GNAS

Abstract: Patients diagnosed with pseudohypoparathyroidism type Ia (PHP Ia) suffer from hormonal resistance and abnormal postural features, in a condition classified as Albright hereditary osteodystrophy (AHO) syndrome. this syndrome is linked to a maternally inherited mutation in the GNAS complex locus, encoding for the GTPase subunit Gsα. Here, we investigated how platelet phenotype and omics analysis can assist in the often difficult diagnosis. By coupling to the IP receptor, Gsα induces platelet inhibition via adeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Earlier analyses indicated that the platelet proteome from healthy subjects is quite stable with < 15% of changes 51 . Similarly, the global platelet proteomes from the few patients, extensively studied so far—such as Albright hereditary osteodystrophy, Glanzmann or Scott syndrome patients—showed only minor changes compared to that of control subjects 27 , 28 , 48 . the technical abilities to study this in the future is made in the revised discussion (page 16).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Earlier analyses indicated that the platelet proteome from healthy subjects is quite stable with < 15% of changes 51 . Similarly, the global platelet proteomes from the few patients, extensively studied so far—such as Albright hereditary osteodystrophy, Glanzmann or Scott syndrome patients—showed only minor changes compared to that of control subjects 27 , 28 , 48 . the technical abilities to study this in the future is made in the revised discussion (page 16).…”
Section: Discussionmentioning
confidence: 94%
“…https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5054341/ b. Supplemental Table 1 and 2 : identified phosphopeptides and proteins c. ProteomeXchange repositories PXD002883 and 10.6019/PXD002883 Cohort 5 28 a. https://www.nature.com/articles/s41598-020-68379-3#Sec25 b. Datafile S1 and Datafile S2 : identified phosphopeptides and proteins c. ProteomeXchange repository PXD016534 Cohort 6 29 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphotyrosine profiling shows that total cellular tyrosine phosphorylation increases upon stimulation with ATP, and is near completely abolished by concurrent treatment of cells with PKAactivating prostacyclin analogue iloprost [48]. This suggests that kinase activity does not indiscriminately result in enhancement of platelet functions, as is often thought.…”
Section: G-protein Coupled Receptor Signalingmentioning
confidence: 77%
“…The more limited ability of iloprost to revert the CRP-XL induced aggregation (in comparison to TRAP6) can be explained by the longer Ca 2+ signal with this GPVI agonist, implying a lower ability of PKA to overrule this signal. On the other hand, our laboratories have described that iloprost and other cAMP-elevating agents, as a pretreatement, are able to affect the collagen-induced platelet adhesion under stasis and flow conditions [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%